Confronting the Communist Past in Macedonia: New Injustices in the Name of Justice - Krtolica, Marko (Serbian Political Science Association (SPSA), 2022)
The fall of Yugoslavia has opened the door to the creation of an independent and democratic Macedonian state. With this opening, the Macedonian political elites have faced a great number of challenges. Among them, the issue which was particularly prominent was the confrontation with the communist past/heritage. Interestingly, over the years the Macedonian political elites had a completely different approach to this issue. During the 90s, the party that emerged from the bosom of the Communist Party decided to ignore this issue. The change of the government in 1998 contributed to the start of certain steps in confrontation with the problematic communist past in Macedonia. Still, such steps were undertaken too slowly, softly and insufficiently. In the end, such an approach of the Macedonian political elites has paved the road for facing the communist past to be misused for revenge and for political party purposes. Such misuse was performed after 2006 through the implementation of the scandalous process of lustration, as well as, by abusing the fate of the victims of the communist regime. The process of lustration especially through its creation and implementation, contrary to the recommendation of the international organizations, had produced new wounds and injustices for the Macedonian society. Additionally, providing moral satisfaction for the communist victims through the project called “Skopje 2014” was overshadowed by a great number of corruptive scandals connected to this project. Thus, the Macedonian story of confronting the communist past has become another sad story of the Macedonian transition – Issue abused for political points and financial motives, not for the promotion and provision of justice, reconciliation and democracy.